ANALISIS SWOT SEBAGAI DASAR PERUMUSAN STRATEGI BERSAING PADA PRODUK ASURANSI JIWA PERORANGAN AJB BUMIPUTERA 1912 KPR PEKANBARU - Putriani, Dian; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in the Individual Life Insurance 1912 KPR Pekanbaru. These businesses engaged in services which compete to provide quality products and good service. With more and more competition in the insurance business makes Individual Life Insurance 1912 KPR Pekanbaru have to compete and survive in the business competition.This study aims to determine the SWOT analysis as the basis for the formulation of a strategy to compete in the Individual Life Insurance 1912 KPR Pekanbaru. This research is descriptive research with qualitative approach and data collection techniques performed by interviewing the parties involved in this study.From the results of SWOT analysis can be seen that there are several alternative strategies that can be used as a tool to win the competition, and the results of this analysis to formulate strategic alternatives for Individual Life Insurance 1912 KPR Pekanbaru long term.Keywords: SWOT analysis, alternative strategies